MARITIME HISTORY: MAMLUK AND ITALIAN INTERACTIONS IN THE PORT CITY OF ALEXANDRIA FROM 1250 TO 1517 - Darmawan, Budi; Shukor, Khairunnisa Binti A; Nazra, Endah Regita Cahyani (Khazanah: Jurnal Sejarah dan Kebudayaan Islam, 2025)
This study investigates the strategic role of Alexandria as a major port city during the Mamluk Sultanate from 1250 to 1517 and the dynamics of its interactions with the Italian maritime republics. Alexandria served as a crucial node in premodern global trade networks. The study also examines the condition of the port and its influence on urban development, maritime security, and state fiscal policy. Drawing on primary sources such as the chronicles of al Maqrizi and Ibn Taghribirdi, as well as secondary studies, the research shows that relations between the Mamluks and the Italian states were shaped by deep economic interdependence. The Mamluks relied on European precious metals and manufactured products, while the Italian states depended on spices, sugar, cotton, and other Eastern commodities that flowed through Alexandria. These interactions unfolded in a tense geopolitical environment marked by the legacy of the Crusades, competition among Italian states, church embargoes, and persistent piracy. The study argues that Alexandria functioned not only as an economic hub but also as a stage for coercive diplomacy, where the Mamluks used foreign merchant communities as instruments of negotiation to compensate for their limited naval power. Yet the reliance on trade monopolies, transit taxation, and the failure to adapt to global changes, especially the rise of Portuguese sea routes and Ottoman expansion, weakened this system and contributed to its fragility in the decades before the fall of the Mamluk Sultanate in 1517